Lower Genital Tract Infections in Pregnant Women: Epidemiology and Risk Factors Associated in Dakar, Senegal - Ndeye Safietou Ngom; Gora Lo; Assane Dieng; Doudou Georges Massar Niang; Serigne Mbaye Lo Ndiaye; Alioune Tine; Awa ba-Diallo; Omar Gassama; Halimatou Diop-Ndiaye; Makhtar Camara (Recent Trends in Infectious Diseases, 2024)
Vaginal infections are responsible for many problems in women of childbearing age and significantly influence pregnancy outcomes. This study sought to ascertain the prevalence of lower genital tract infections and the risk factors associated with them in pregnant women under observation at the Nabil Choucair Health Centre in Dakar, Senegal. This nine-month cross-sectional study, which involved women between 34 and 38 weeks gestation (WG), was carried out from July 2020 to March 2021. The vaginal samples were analyzed using the humid montage method, Gram coloration (Nugent criteria), and culture in a specific medium. The data was analyzed using SPSS version 25 and the chi-two test to determine the strength of the association. A significance level of p < 0.05 was set for the statistical tests. Microbiological confirmation of infection was found in 227 pregnant women, resulting in an overall prevalence of 59.1% (227/384). In the series, the median gestational age was 36 WG. Only 55.9% (215/384) of patients reported infection-related symptoms. With 42.7% (164/384) of these infections being vulvovaginal candidiasis, it was the most frequent, followed by bacterial vaginosis (29.2%; 112/384) and Trichomonas vaginal (1.3%; 5/384). Mixed infections were recorded at 24.8% (n = 94), with a Gardnerella vaginalis/Candida spp. co-infection rate estimated at 13.80% (n = 53). Other germs found in mixed infections included Group B Streptococcus (GBS; 8.07%; n = 31) and Escherichia coli (0.78%; n = 3). Clinical symptoms (p = 0.018), bleeding from ectocervical contacts (p = 0.005), and unfavorable pregnancy outcomes (p = 0.020) were significantly correlated with the occurrence of lower genital tract infections. Our findings show a high prevalence of vaginal infections during pregnancy. Vaginal sampling during pregnancy should be included in the prenatal surveillance program to reduce the disease burden and complications associated with lower genital tract infections.
Keywords: Associated risk factors; Lower genital infections; Pregnant women; Senegal